Provisional stenting with side branch rescue stenting is associated with increased 3-year target lesion failure in patients with acute coronary syndrome and coronary bifurcation lesions - Sheiban, Imad; Ge, Zhen; Kan, Jing; Zhang, Jun-Jie; Santoso, Teguh; Munawar, Muhammad; Ye, Fei; Tian, Nailiang; Chen, Shao-Liang (Frontiers in Cardiovascular Medicine, 2022)
Background: Provisional stenting (PS) is the main treatment for coronary bifurcations for great majority of coronary bifurcation lesion and includes PS with 1-stent and PS with 2-stent. However, the treatment difference between PS with 1- vs. with 2-stent remains unclear in patients with acute coronary syndrome (ACS) and coronary bifurcation lesions. Methods: Overall, 820 ACS patients with Medina 1,1,1 or 0,1,1 coronary bifurcation lesion who had completed 3-year follow-up were included and assigned to the PS with 1-stent (n=519) or the PS with 2-stent (n=301) according to the use of final stenting technique. The primary endpoint was the target lesion failure (TLF) at 3-year since stenting procedures. Results: At 3-year follow-up, TLF occurred in 85 (16.4%) patients in the PS with 1-stent group and 69 (22.9%) in the PS with 2-stent group (hazard ratio [HR] 1.52, 95% confidence interval [CI], 1.06–2.17, p=0.021), mainly driven by higher rate of target lesion revascularization (TLR) in the PS with 2-stent group (13.0% vs. 8.3%, HR 1.65, 95% CI 1.04-2.61, p=0.033). Complex bifurcations, side branch (SB) pretreatment, intravascular imaging-guidance, and hyperlipidemia were four predictors for 3-year TLF. SB pretreatment was associated with increased 3-year TLR, leading to extreme higher 3-year TLF. Conclusions: Provisional with 2-stent for ACS patients is associated with higher rate of 3-year TLF, mainly due to increased requirement ofrevascularization. SB pretreatment should be avoided for simple bifurcation lesion.